Beyond reductionism: the emerging holistic paradigm in indirect control of pathogen infection - Jang, Seonghan; Kim, Dajeong; Seo, Hwi Won; Ryu, Choong-Min (Frontiers in Microbiology, 2025)
Microbial research has often emphasized direct interactions between pathogens and other microbes, leading to the discovery of antibiotics and biological control agents. However, such approaches frequently overlook the complexity of microbial ecosystems and show limited effectiveness in real-world settings. Indirect interactions, where non-pathogenic microbes influence pathogen behavior through ecological networks, offer an alternative strategy for controlling infectious diseases. We hypothesize that targeting microbes support or influence pathogen activity, rather than the pathogen itself, can lead to more effective and sustainable disease control. Indirect modulation of pathogen behavior through ecological networks may reduce virulence, persistence, and resistance development. Recent studies in both animal and plant systems support this idea, showing that manipulating non-pathogenic microbial relationships can suppress disease occurrence more efficiently than direct intervention. Focusing on indirect ecological relationships allows for a more comprehensive understanding of pathogen dynamics and presents new opportunities for sustainable disease management.